(untitled) (Fiep Bulletin - online, 2011)
The present work developed a case study that objectified to identify the viability and relevance of the introduction of the discipline Nautical Sports in the curricular grade of the course of Physical Education in Veiga de Almeida university in Cabo Frio/RJ campus. It was verified, that the situation of the work market in this region, to identify the capacity of absorption of the professionals just graduated and future graduated. It was developed an evaluation of the structural possibilities and of localization of the entity of education in receiving this discipline and still an implantation proposal and the summary of discipline, for contact with the institution and its customers. To complement the study and to raise information, on the interest of students for it discipline, was elaborated a research with this objective in the format of interview for the group of the sixth period of the day and the night – turn of this university. With the refined data, it was developed a proposal that was presented to the students and with its result, later, was presented to the direction of the institution. It was verified that the entity and its customers had demonstrated interest in the introduction of this discipline and are concluded, after analyzes of all the data that the introduction of disciplines nautical sports is viable and excellent.